Optimalisasi Kandungan Kalsium Mie Kering dengan Substitusi Tepung Tempe dan Tepung Tulang Ikan Lele - Amilenia Nurlaila; Annis Catur Adi (Media Gizi Kesmas, 2023)
Background: Adolescents need good nutrition for their physical growth, one of which is protein and calcium. In this study, dry noodle formulation was carried out by substituting tempeh flour and catfish bone flour. Noodles are a food that is much loved by teenagers because it contains high energy, carbohydrates, and fat but low content of other nutrients. Objectives : This study aims to determine the effect of the substitution of tempeh flour and catfish bone meal on the acceptability and nutritional calcium value of dry noodles. Methods : The experimental design used was a completely randomized design (CRD). The research carried out in the formula development stage was true experimental research (pure experimental) and in the acceptance testing stage, the formula was using quasi-experiments. This study used untrained panelists, namely teenagers totaling 25 people. The analysis in this study used descriptive analysis and statistical analysis by Kruskal Wallis. Result : The percentages of substitution of tempeh flour and catfish bone meal were F1 (7.5% tempeh flour, 2.25% catfish bone meal), and F2 (15% tempeh flour, 1.5% catfish bone meal). Based on the test results for the acceptability of dry noodle products with the substitution of tempeh flour and catfish bone flour by untrained panelists, the results with the highest score were F1. The results of the Kruskal Wallis statistical test showed that there was a significant difference (pâ‰¤0.05) in the level of preference in the aspects of color, aroma, texture, and taste. The nutritional value for 100 grams of dry noodles with substitution of tempeh flour and catfish bone meal (Energy: 357.87 kcal; Calcium 139.8 mg) is able to meet 10-15% of the daily needs of adolescents. Conclusion : Dried noodles with 15 grams of tempeh flour and 3 grams of catfish bone flour have good acceptability with high calcium content and are suitable as alternative snacks for teenagers.